THE QUALITY MANAGEMENT SYSTEM AS A MODERN APPROACH TO MANAGEMENT OF EDUCATION - Tatyana A. Oleynikova; Alla I. Ovod; Victoria A. Solyanina (Высшее образование в России)
The management of education quality supposes the administration of both the results and every stage of the educational process that can be provided in the present conditions only by the existence of an efficient quality management system (QMS) regarded as a basis for reaching the set goals, transferring to a new level of labor organization, control and administration of the process and the result of specialists training.The certified quality management system guarantees the quality of the educational process for the existing and potential consumers and serves as a basis for the competitive advantages of the university.